2000
DOI: 10.1128/iai.68.6.3630-3634.2000
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogenic Toxin Superantigen Site Specificity in Toxic Shock Syndrome and Food Poisoning in Animals

Abstract: Staphylococcus aureus and Streptococcus pyogenes express pyrogenic toxin superantigens (PTSAgs) that are associated with toxic shock syndrome (TSS) and staphylococcal food poisoning (SFP). Most PTSAgs cause TSS in deep-tissue infections, whereas only TSS toxin 1 (TSST-1) is associated with menstrual, vaginal TSS. In contrast, SFP has been linked only with staphylococcal enterotoxins (SEs). Because of the differential abilities of PTSAgs to cause systemic or localized symptoms in a site-dependent manner, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 30 publications
(21 reference statements)
3
91
0
2
Order By: Relevance
“…Our current study was designed to further define residues important for the functional interaction of TSST-1 with the TCR by alanine scanning mutagenesis. Our data suggest that residues Tyr 13 136 , and Gln 139 are individually crucial for direct binding to hV␤2.1. Due to the location of these residues, we propose a model in which the MHC/TSST-1/TCR ternary complex is similar to the ternary complex of SEB, SEC, and SPE A, yet the TSST-1 complex may allow for direct interactions between the CDR3 loop of the TCR ␤-chain and TSST-1.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Our current study was designed to further define residues important for the functional interaction of TSST-1 with the TCR by alanine scanning mutagenesis. Our data suggest that residues Tyr 13 136 , and Gln 139 are individually crucial for direct binding to hV␤2.1. Due to the location of these residues, we propose a model in which the MHC/TSST-1/TCR ternary complex is similar to the ternary complex of SEB, SEC, and SPE A, yet the TSST-1 complex may allow for direct interactions between the CDR3 loop of the TCR ␤-chain and TSST-1.…”
mentioning
confidence: 66%
“…The slight decrease in hV␤2.1 binding seen for mutations at positions Tyr 13 , Tyr 115 , and His 141 may indicate minor involvement in the TCR/TSST-1 complex, probably through stabilizing interactions. Based on the cocrystal structure of SEC3 in contact with the mouse 14.3.d ␤-chain (21), the mutation of all SEC3 residues involved in contact with the ␤-chain revealed that only two of 12 residues (N23A, Q210A) completely lost detectable binding using their criteria for stimulatory capacity, while a third mutation (F176A) had barely detectable mitogenic activity (5).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The staphylococcal superantigen TSST-1 is believed to be responsible for ∼100% of menstrual-TSS cases, which is likely related to the apparent unique ability of this particular superantigen to cross mucosal barriers (6,29). Key host and environmental factors known to influence the development of staphylococcal TSS include elevated oxygen and carbon dioxide levels, the presence of proteins, neutral pH, and 37°C (2).…”
Section: Discussionmentioning
confidence: 99%